Transformation urbaner Infrastrukturen - (:unkn) unknown (My University, 2023)
The transformation of urban infrastructures, such as water, energy and transport, is central for the sustainable development of cities. Those responsible for the provision of public services are increasingly under pressure to transform infrastructures to make them more sustainable. Our paper explores governance-related challenges and solutions to transforming urban infrastructures in the context of the city state of Berlin. In the form of case studies, we investigate three transdisciplinary research projects that attempt to support transformation processes in the water, energy and transport sectors respectively. The analysis draws on reports and publications, discussion with central actors from the projects as well as the city administration between 2017 and 2022. Despite differences between the projects as well as the infrastructure systems addressed, we identify some common barriers for the transformation of urban infrastructures in the city state of Berlin. Results show that local neighbourhoods are important socio-spatial units for catalysing transformation processes. They allow for experiments with more sustainable infrastructure configurations and novel governance approaches. However, these niche experiments do not scale to the mainstream, yet. Across the three infrastructure systems, we discuss potential solutions and conclude with reflections on the implications for the sustainable transformation of urban infrastructures in Berlin and beyond.
Hemmnisse und Lösungsansätze aus drei transdisziplinären Forschungsvorhaben zu netzgebundenen Infrastrukturen in Berlin
Keywords: Infrastrukturplanung; Transformation; Nachhaltige Stadtentwicklung; Wärmeinfrastruktur; Verkehrsinfrastruktur; Wasserinfrastruktur